Wound Healing Potential of Curcumin and Colostrum- Loaded Liposomes in Diabetic Foot Ulcers - Chawla, Isha; Zahoor, Ishrat; Bansal, Seema; Nair, Anroop B; Gupta, Sumeet (Indian Journal of Pharmaceutical Education and Research)
Background: Diabetic Foot Ulcers (DFUs), a serious diabetes consequence, are caused primarily by hyperglycemia, oxidative stress, and chronic inflammation. This study aims to evaluate the therapeutic potential of liposome-based formulations containing curcumin, colostrum, or both for oral and topical delivery in DFU management. Materials and Methods: The thin film hydration approach was used to develop the liposomes, and their pharmaceutical characteristics were assessed. These liposomes were modified into hydrogels. Efficacy was evaluated in diabetic rats by measuring blood glucose, body weight, antioxidant status (SOD, CAT, GSH, MDA), HbA1c, insulin, TNF-α levels, wound contraction, histopathology, and TNF-α protein expression. Results: Liposome-loaded hydrogels were pH-compatible and rheologically suitable for topical use. Glycemic control was significantly improved (p<0.0001) with the colostrum-curcumin combination in oral and topical therapy. A highly significant improvement in antioxidant levels (p<0.0001) was noticed in both oral and topical administration of curcumin and colostrum combination, compared to the positive control group. In addition, the combination reduced the TNF-α levels considerably in oral (64.3%) and topical (77.1%). Higher wound contraction, rapid re-epithelialization, and collagen deposition were also observed with the combination. Conclusion: In conclusion the developed curcumin-colostrum-loaded liposomes showed a synergistic effect and could be a novel delivery platform for DFU therapy.
Keywords: Colostrum; Curcuma; Liposomes; Oral; Topical; Hydrogel; Inflammatory Marker; Oxidative Injury; Foot Ulcers.